Η ΡΙΖΟΣΠΑΣΤΙΚΗ ΔΕΞΙΑ ΚΑΙ ΤΟ ΑΓΡΟΤΙΚΟ ΖΗΤΗΜΑ ΣΤΙΣ ΑΡΧΕΣ ΤΟΥ ΕΙΚΟΣΤΟΥ ΑΙΩΝΑ. Η ΠΕΡΙΠΤΩΣΗ TOΥ ΧΡΗΣΤΟΒΑΣΙΛΗ ΚΑΙ ΤΗΣ ΕΤΑΙΡΕΙΑΣ «ΕΛΛΗΝΙΣΜΟΣ» - ΠΟΤΑΜΙΑΝΟΣ ΝΙΚΟΣ (Μνήμων, 2004)
Nikos Potamianos, The Radical Right and the Agrarian Question in the Early 20th Century. The Case of Christovassilis and the "Hellenism Asosociation" The subject of this article is an aspect of the history of the radical right in Greece, namely its intellectual and political response to the agrarian question which emerged in Greece at the end of the 19th century after the incorporation of new provinces where large landownership was predominant. In particular, the arguments and theses of a cadre of the biggest nationalist league of Athens in 1907 are examined, in contrast to its earlier views on the agrarian question and in contrast to the discourse of the radical supporters of the sharecroppers as well as the landowners. Christovassilis adopts a pro-peasant stand, attacking capitalist landowners and indirectly proposing the purchase of the land by its cultivators with the assistance of the state. However, his main aim was to prove that parliamentary democracy was incapable of improving the sharecroppers’ situation, a task which only an authoritarian state could accomplish. Crucial in Christovassilis’ arguments was the use of nationalist discourse in order to legalize sharecroppers’ demands: he linked the peasants’ struggle for land in the past with the national conflict with the Ottoman conquerors, equating land with fatherland and, therefore, the ownership of land of Thessaly with the peasants’ participation in the nation. Christovassilis’ earlier views which put emphasis on the social aspects of the agrarian question gave way to the pre-ponderance of the nationalist argument, which was in turn related to other aspects of the ideology of the radical right. "Hellenism" followed a strategy of appealing to the mobilized subordinate classes — but without totally adopting their point of view. It was always clear that the viewpoint of the association was that of paternalism, not of emancipation. One of the points of its criticism against the democratic state was that the latter was not powerful enough torepress the impending peasant revolt. The restoration of law and orderwas for the radical right more important than the improvement of the living conditions of the lower strata. And the adoption of popular demands, in general, proved to be merely rhetoric: when the class struggle became more intense, especially in the case of the agrarian movementof 1910, "Hellenism" remained aloof.